Interactive e-module with reinforcement method to improve discipline in early childhood - Jihan Faninda Ridanti; Hadiyanto Hadiyanto; Delfi Eliza; Setiyo Utoyo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Discipline is a fundamental aspect of early childhood character development, especially in kindergarten settings. Observations and an open-ended questionnaire conducted at TK IT Abatatsa Lahat showed that children often arrived late, left their belongings unattended, struggled to follow classroom rules, and found it difficult to wait their turn. Teachers also reported limited knowledge of reinforcement strategies and expressed the need for practical guidance. This study aimed to develop and evaluate a reinforcement-based interactive e-module to support kindergarten teachers in fostering children’s discipline. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Quantitative data were used to assess instrument validity, product validity, practicality, and effectiveness, while qualitative data from observations, interviews, expert feedback, and a Focus Group Discussion (FGD) informed product refinement throughout the development process. The large-group trial involved 20 children from Group B at TK IT Abatatsa Lahat, the small-group trial included 15 children from TK IT Abatatsa Lahat Selatan, and the study also involved three expert validators and 12 kindergarten teachers. The developed e-module demonstrated high validity, with content and media validity scores of 95.38% and 94%, respectively. Teacher evaluations showed good practicality (82.5%), while the FGD produced a practicality score of 87.92%. The effectiveness test revealed that children taught using the e-module achieved a discipline score of 90.37%, compared with 64.56% in the comparison group. Qualitative findings further indicated that the module’s structured, step-by-step approach improved teachers’ confidence and consistency in applying reinforcement. Overall, the interactive e-module provides a practical, evidence-based, and teacher-friendly resource for strengthening discipline in early childhood education.